2009
DOI: 10.1086/597399
|View full text |Cite
|
Sign up to set email alerts
|

Multistate Outbreak ofEscherichia coliO157:H7 Infection Associated with Consumption of Packaged Spinach, August–September 2006: The Wisconsin Investigation

Abstract: The rapid multijurisdictional epidemiologic and laboratory response, including timely pulsed-field gel electrophoresis pattern analysis and PulseNet posting, facilitated prompt voluntary recall of brand A spinach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(106 citation statements)
references
References 30 publications
0
104
2
Order By: Relevance
“…Between 1992 and 2006, 2,274 foodborne outbreaks of infectious intestinal disease were reported in England and Wales, 82 (4%) of which were associated with the consumption of prepared salads (24). It is widely recognized that uncooked salad vegetables can be a cause of foodborne infectious disease (25)(26)(27). Although there are few reports specifically identifying watercress as being associated with cases of bacterial foodborne disease, a previous review of risk factors for STEC O157 cases in England and Wales demonstrated that consumption of watercress was associated with infection (28).…”
Section: Resultsmentioning
confidence: 99%
“…Between 1992 and 2006, 2,274 foodborne outbreaks of infectious intestinal disease were reported in England and Wales, 82 (4%) of which were associated with the consumption of prepared salads (24). It is widely recognized that uncooked salad vegetables can be a cause of foodborne infectious disease (25)(26)(27). Although there are few reports specifically identifying watercress as being associated with cases of bacterial foodborne disease, a previous review of risk factors for STEC O157 cases in England and Wales demonstrated that consumption of watercress was associated with infection (28).…”
Section: Resultsmentioning
confidence: 99%
“…PCR genotyping demonstrated that each of the 39 Missouri and Kansas case isolates belonged to E. coli O157:H7 phylogenetic cluster 1. Cluster 1 has two main branches (14), the 87-14 lineage, named for an E. coli O157:H7 strain recovered in Washington State in 1987, and the TW14359 lineage, named for an E. coli O157:H7 strain associated with a nationwide outbreak attributed to spinach in 2006 (19).…”
Section: Resultsmentioning
confidence: 99%
“…However, a large outbreak (.4000 cases) of gastroenteritis and HUS belonging to an unusual (O104:H4), non-O157 STEC strain, predominantly affecting adults (89%), recently occurred in Germany (7). More than 25% of cases developed HUS, a proportion that is much higher than in previous outbreaks (8)(9)(10). The E. coli O104:H4 strain combines virulence potentials of enteroaggregative E. coli with a characteristic "stacked-brick" pattern of adherence to intestinal epithelial cells and of typical Stx-producing enterohemorrhagic E. coli (11).…”
mentioning
confidence: 99%